Thursday
March 23, 2017

Post a New Question

Posted by on Wednesday, January 11, 2012 at 9:10am.

verify that the function f and g are inverse of each other by showing f(g(x)) and g(f(x)) =x

f(x)= 6-2/5x g(x)=15-5/2x

  • math - , Wednesday, January 11, 2012 at 5:30pm

    just plug and chug:
    (I rewrite 2/5x as 2x/5 to avoid ambiguity)

    f(g) = 6 - 2g/5 = 6 - 2(15 - 5x/2)/5
    = 6 - (30 - 5x)/5 = 6 - (6 - x) = x

    g(f) = 15 - 5f/2 = 15 - 5(6 - 2x/5)/2
    = 15 - (30 - 2x)/2 = 15 - (15 - x) = x

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question